Islamic Religious Education in Perspective Urban Society: Analysis of Factors Influencing Parents' Decisions Choosing an Islamic Religious Education Institution at Mataram City - Mutawalli, (TADRIS: Jurnal Pendidikan Islam, 2022)
This study was driven by the growing interest of students’ parents in Islamic boarding schools in recent years in the capital city of Mataram, West Nusa Tenggara. It was evidenced by the gap between the number of Islamic schools and the number of applying students and accepted with the ratio of 1:5 (one accepted out of five applicants). This trend was also proven by the emergence of integrated schools, Tahfiz schools, Qur’anic schools, Islamic kindergarten and etc. This study aimed to examine the factors affecting the parents’ decision in sending their children to Islamic boarding schools in the city of Mataram. This study drew on the descriptive quantitative method that analyzed the data through multiple linier regression, F test and t-test. The statistical evidence showed that motivation (x1) and perceptions (x2) significantly influenced the parents’ decision to send their offspring to the Islamic schools (Y) in the capital city with 45% (motivation) and 51% (perceptions). It was also found that economic factor (x3) did not significantly influence their decision with only 29% contributing factor. This was caused by 62% of the parents having adequate permanent jobs and high levels of education from senior secondary to doctorate degree. The most influential factor for enrolling their children was the parents’ perceptions (x2) as evidenced by the value r= 51 or 51%, followed by motivation (X1) with 45%, and economic factor (X3) with 29%. This study also unveiled that the percentage of schooling preferences of the parents according to the school levels varied from SDIT/MI 37.2%, MTs/SMPIT 33.5%, and MA/SMAIT 29.3%.